Making sense of change management : a complete guide to the models, tools and techniques of organizational change - Cameron, Esther; Green, Mike, 1959- (2015)
"Making Sense of Change Management is the best-selling classic text, providing a thorough overview of the subject of change for both students and professionals. Along with explaining the theory and practice of change management and comprehensively covering the models, tools, and techniques of successful change management, this completely revised and updated fourth edition includes more international examples and case studies throughout the book. The chapter on cultural change has been re-written to reflect the emerging new thinking and practice in this area, offering ways to help managers implement cultural change processes within their organization. It also explores cultural sensitivity and what to do when cultures collide.Additionally, the chapter on IT based process change has now been replaced with one on the inter-relationship with project management (PM) and change management. It defines "project success," explains how PM approaches are increasingly being used to manage transformational change, and covers complexity models, agile approaches, and stakeholder management.With free online resources for professors/instructors, this is an ideal textbook for MBA or graduate students focusing on leading or managing change"--
"The world we live in continues to change at an intense rate. In order to succeed over the next few years, organizations must adapt to tough market conditions by changing their strategies, their structures, their boundaries and of course their expectations of staff and managers. Ideal reading for anyone who is currently part of or leading a change initiative, Making Sense of Change Management, 4th edition, is the definitive text in the field of change management. Aimed at students and professionals alike, it provides comprehensive coverage of the models, tools and techniques of successful change management with a focus on individual, team and organizational change to help the reader apply each concept to unique situations. Now with a new chapter exploring the integration of change management with project management, it also contains a completely revised and updated chapter on culture change that takes into account emerging thinking and practice"--
Includes bibliographic references and index
Keywords: Organizational change -- Management; Teams in the workplace -- Management; Reengineering (Management); Information technology -- Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Leadership; PSYCHOLOGY / Industrial & Organizational Psychology